The Campylobacter jejuni Type VI Secretion System Enhances the Oxidative Stress Response and Host Colonization - Liaw, Janie; Hong, Geunhye; Davies, Cadi; Elmi, Abdi; Sima, Filip; Stratakos, Alexandros; Stef, Lavinia; Pet, Ioan; Hachani, Abderrahman; Corcionivoschi, Nicolae; Wren, Brendan W.; Gundogdu, Ozan; et al. (Frontiers in Microbiology, 2019)
The role of the Type VI secretion system (T6SS) in Campylobacter jejuni is poorly understood despite an increasing prevalence of the T6SS in recent C. jejuni isolates in humans and chickens. The T6SS is a contractile secretion machinery capable of delivering effectors that can play a role in host colonisation and niche establishment. During host colonisation, C. jejuni is exposed to oxidative stress in the host gastrointestinal tract, and in other bacteria the T6SS has been linked with the oxidative stress response. In this study, comparisons of whole genome sequences of a novel human isolate 488 with previously sequenced strains revealed a single highly conserved T6SS cluster shared between strains isolated from humans and chickens. The presence of a functional T6SS in the 488 wild-type strain is indicated by expression of T6SS genes and secretion of the effector TssD. Increased expression of oxidative stress response genes katA, sodB, and ahpC, and increased oxidative stress resistance in 488 wild-type strain suggest T6SS is associated with oxidative stress response. The role of the T6SS in interactions with host cells is explored using in vitro and in vivo models, and the presence of the T6SS is shown to increase C. jejuni cytotoxicity in the Galleria mellonella infection model. In biologically relevant models, the T6SS enhances C. jejuni interactions with and invasion of chicken primary intestinal cells and enhances the ability of C. jejuni to colonise chickens. This study demonstrates that the C. jejuni T6SS provides defence against oxidative stress and enhances host colonisation, and highlights the importance of the T6SS during in vivo survival of T6SS-positive C. jejuni strains.